Joaquín Edwards Bello: the broken letters - García-Arango, Lis (Árboles y Rizomas, 2020)
The article describes Joaquín Edwards Bello’s characterization of the Chilean mass media in his novel El Roto (1920). The analysis aims to summarize the features of the Chilean journalistic and literary field during the first decades of the twentieth century, according to the literary version of the author and the review of the literary, historical and communications critique of the epoch. Methodologically, scenes of interest (those that actually happen in newspapers or where the characters read) are selected to identify the agent readers. Then, these characters’ behavior is analyzed from the perspective of the theory of communication (in particular, according to the tenets of hypodermic theory, uses and gratifications, and the social theory of communication). It is concluded that in El Roto the characters prioritize reading the press over reading books; this practice acts as a desire-producing agent based on models to imitate; that is, in the words of René Girard in his Mentira Romántica y verdad novelesca (1963), mimetic desire.